Ag-Innovation Data Hub - Risk Reporting and Emergency Response Management System - Wilson, Michael; Dalaa, Mustapha Alasan; Tepa Yotto, Ghislain (2025)
This Info graphic presents a risks reporting and emergency response system integrated into Ghana's Ag-Innovation data hub enabling the swift communication within the early warning and rapid response system for pests and diseases (EWRRS-PD) in Ghana.